Post-COVID-19 adoption of service robots in Thai tourism enterprises: Assessing impacts on job displacement and job creation - Pungpond Rukumnuaykit; Piriya Pholphirul; Worawut Phaphimolwat (Social Sciences and Humanities Open, 2025)
As the COVID-19 pandemic recedes, the tourism sector has increasingly integrated modern technologies, particularly service robots, sparking concerns about potential impacts on employment, especially in developing countries where tourism is heavily reliant on labor-intensive workforces. A field survey conducted across five sectors in 10 major tourist provinces in Thailand reveals that high-revenue companies are more inclined to adopt advanced technologies compared to their lower-revenue counterparts. The analysis indicates that workers in larger firms, especially in the hotel and accommodation sectors, are more vulnerable to job displacement, with unskilled workers being the most susceptible to replacement by technology. To address this issue, policymakers should prioritize upskilling initiatives that enhance digital literacy and customer service skills, foster human-technology collaboration through hybrid work models, and offer incentives for companies to maintain human-centered roles.